Asymmetric synthesis of S(IV) and S(VI) stereogenic centers - Zhang, Xin (2023)
Sulfur can form diverse S(IV) and S(VI) stereogenic centers, of which some have gained significant attention recently due to their increasing use as pharmacophores in drug discovery programs. The preparation of these sulfur stereogenic centers in their enantiopure form has been challenging, and progress made will be discussed in this Perspective. This Perspective summarizes different strategies, with selected works, for asymmetric synthesis of these moieties, including diastereoselective transformations using chiral auxiliaries, enantiospecific transformations of enantiopure sulfur compounds, and catalytic enantioselective synthesis. We will discuss the advantages and limitations of these strategies and will provide our views on how this field will develop.